A Systematic Review of Lean Six Sigma Implementation in Food Industry - Najihah Azalanzazllay, Nurul; Abdul Halim Lim, Sarina (International Journal of Engineering and Technology, 2019)
Lean Six Sigma (LSS) is the most current quality management approach being applied recently in many industries to improve food quality and subsequently process excellence in the businesses. The objectives of this paper are to determine the barriers and resistance to change factors of implementing LSS approach in the food industry. This study was conducted as to determine the benefits of applying LSS and comparing the trend of quality management being used in the food industry. It is also based on the application of systematic review of 113 LSS articles, involving a structured approach of data collection and data extraction. The listed barriers and resistance to change factors shown are top management support, lack of quality improvement knowledge, poor training and insufficient skills amongst employees and lack of financial budget thus causing the limitation of LSS approach in the food industry. The result mapped the current quality management approaches implemented in the food industry. The academics and the food industry practitioners may have an insight from this paper by considering their critical success factors, barriers and resistance to change factors that could facilitate towards a successful LSS implementation.Â Â Â